Theorizing the "Home" in Homeschooling: Pragmatist Analyses of the Family, Education, and Civic Belonging. Issue 3 (8th September 2021) - Greenwalt, Kyle
Abstract: Over the past twenty‐five years, homeschooling has been growing in popularity. Conventionally, the actions of homeschoolers are understood as a rejection of the public school — and, by extension, a rejection of participation in the public sphere writ large. Yet such interpretations are made without due attention to the meaning of both "home" and "school" in larger social discourses. This article explores the wisdom of such analyses through an examination of the place and function of home and school in pragmatist views of democracy. Using the thought of John Dewey and Jane Addams, Kyle Greenwalt shows how the relationship between household and school was reconfigured at a key moment in the history of American public education. After demonstrating how this is so, Greenwalt extends his outlook by considering pragmatic thought as it interacts with the Chinese tradition — through the lens of Confucian role ethics. In particular, he argues that Confucian role ethics provides a way of thinking about the family household that emphasizes its civic potential through the promotion of relationships that are fluid, sustainable, and educative. In short, Greenwalt argues for a new way to think about the educative potential of family‐centered, community‐based living.